Latems Kunstleven omstreeks 1920. - Chabot, Georges; Van den Abeele, Raf (Sint-Martens-Latem : Latemse Kunstkring, 1964)
Van den Abeele, Albijn ; Minne, George ; Dessenis, Alfons ; De Smet, Gust ; Aerens, Robert ; Chabot, Georges ; Servaes, Albert ; van den Berghe, Frits ; Permeke, Constant ; Gevaert, Edgar ; De Buck, Evarist ; Lippens, Piet ; Maes, Herman
biografie
Latems Kunstleven omstreeks 1920, Gemeentehuis, Sint-Martens-Latem, 30 mei tot 21 juni 1964
Nederlands
boek